Constructal Human Dynamics,Security and Sustainability - Bejan, Adrian (IOS Press, 2013)
Globalization, security infrastructure and energy sustainability can be designed based on a scientific principle. This book approaches these objectives based on constructal theory, which means to design such projects as global 'flow' architectures that are 'alive' with movement of personnel, equipment, information, and education.